Encyclopedia of Triassic, Jurassic and Cretaceous Periods - Carte, Aliya, author 650157; Grady, Lou, author 650158 (Delhi, India : Academic Studio, 2012)
This book is a complete Encyclopedia of Triassic, Jurassic and Cretaceous Periods.